Teaching Malay word pronunciation skills among international students at Universiti Putra Malaysia using colored syllables - Mohd Sopian, Sofia Hani Izyan; Said, Rozita Radhiah; Jamil, Halimah (Human Resources Management Academic Research Society, 2024)
The Malaysia Education Development Plan 2015-2025 (Higher Education) stated that language skills as one of the attributes that need to be in the students at the higher education level. Students are encouraged to learn an additional global language without sieving proficiency and proficiency in Malay and English (Ministry of Education Malaysia, 2015). At UPM, local students need to learn additional global language skills such as Chinese, Arabic or German, while international students need to pursue Communication Malay (LPM2100) as a graduate compulsory requirement. Teachers in this LPM2100 course lasted for four months in two different classrooms (class A & Class B) that each consisted of 10 international students. Teachers adapted the use of colored syllables to help improve the mastery of Malay pronunciation skills for Class A students while Class B students are taught to spell and stick traditionally. At the end of the teacher semester found the overall performance of international students from Class A are at a better level compared to the overall performance of international students from Class B. This shows that Class A students have better, clear and understandable words spoken. Class A students also successfully ‘detriminate’ the syllables correctly. If viewed on Class B students’ pronunciation skills, they have relatively weak, unclear and sometimes difficult to understand. Based on results can prove that the use of colored syllables is effective in helping to improve the skills of the Malay language pronunciation of international students. The use of colored syllables is easy to use by international students and is easy to operate by teachers in the teaching of Malay pronunciation skills. This way is simple and no maintenance costs are required as software applications or external technologies. Furthermore, the use of colored syllables is capable of attracting international students’ interest and motivation to follow the Malay language PdP compared to their other language courses that only use one color tone, namely black. The use of colors in teaching pronunciation can certainly be of interest to international students.